Writing dissertation and grant proposals epidemiology, preventive medicine and biostatistics [electronic resource] - Chasan-Taber, Lisa (Boca Raton CRC Press/Taylor and Francis, 2014)
Competition for research funds in epidemiology, preventative medicine, and biostatistics has never been more intense and, at the same time, the grant application and review process at such agencies as the National Institutes of Health (NIH) is undergoing significant transformation. Writing Dissertation and Grant Proposals: Epidemiology, Preventive Medicine and Biostatistics targets effective grant proposal writing in this highly competitive and evolving environment. Covering all aspects of the proposal writing process, the text:Provides summary checklists and step-by-s.
Chapter 14: Reproducibility and Validity StudiesChapter 15: Abstracts and Titles; Chapter 16: Presenting Your Proposal Orally; Chapter 17: Choosing the Right Funding Source; Chapter 18: Submission of the Grant Proposal; Chapter 19: Review Process; Chapter 20: Resubmission of the Grant Proposal; Back Cover.
Includes bibliographical references and index.
Keywords: Epidemiology -- Research grants; Proposal writing for grants; Proposal writing in medicine; Public health -- Statistical services -- Research grants; Financing, Organized; Language Arts & Disciplines -- Composition & Creative Writing; Language Arts & Disciplines -- Rhetoric; Reference -- Writing Skills; Electronic books